The Development of SOLO Taxonomy Based Assessment Tool on Text of Observation Reports of X Grade Students of Senior High School 1 NA. IX-X - Nining Mindayani; Wisman Hadi; Biner Ambarita (BIRCU, 2019)
This study is aimed to describe the process of developing SOLO Taxonomy-based assessment tools on the text of observation reports for X grade students of Senior High School 1 NA. IX-X; describe how the appropriateness of the assessment tool, and describe the effectiveness of the assessment tool. This study uses Borg & Gall development model. The analysis is done by determining the characteristics of the will of students and teachers by determining the percentage of answers to each question / statement. The data obtained in this study were quantitative descriptive data. The results showed that: (1) the development of Solo Taxonomy-based assessment tools on the text of observation report was carried out in several stages, there were: research and information collecting; planning; develop preliminary form of product; preliminary field testing; main product revision; and main field testing. This stages has been restricted to the entire stage of the Borg & Gall development model. Restrictions on the stages of development are tailored to the needs of researchers. All stages are carried out until the product is said to be of good quality based on validity and is suitable for use in learning; (2) the average percentage of all sub-components from the results of the validation of material experts was 81%. The average percentage of all indicators of results to content eligibility was 85.49%; Presentation Feasibility has an average of 88.4%; language worthiness has an average of 90.3%; all three components were in the